Autosomal dominant growth hormone deficiency disrupts secretory vesicles in vitro and in vivo in transgenic mice. - McGuinness, L; Magoulas, C; Sesay, A; Mathers, K; Carmignac, D; Manneville, J; Christian, H; Phillips, J; Robinson, I (2003)
Autosomal dominant GH deficiency type II (IGHDII) is often associated with mutations in the human GH gene (GH1) that give rise to products lacking exon-3 ((Deltaexon3)hGH). In the heterozygous state, these act as dominant negative mutations that prevent the release of human pituitary GH (hGH). To determine the mechanisms of these dominant negative effects, we used a combination of transgenic and morphological approaches in both in vitro and in vivo models. Rat GC cell lines were generated expressing either wild-type GH1 (WT-hGH-GC) or a genomic GH1 sequence containing a G->A transition at the donor splice site of IVS3 ((Deltaexon3)hGH-GC). WT-hGH-GC cells grew normally and produced equivalent amounts of human and rGH packaged in dense-cored secretory vesicles (SVs). In contrast, (Deltaexon3)hGH-GC cells showed few SVs but accumulated secretory product in amorphous cytoplasmic aggregates. They produced much less rGH and grew more slowly than WT-hGH-GC cells. When cotransfected with an enhanced green fluorescent protein construct (GH-eGFP), which copackages with GH in SVs, WT-hGH-GC cells showed normal electron microscopy morphology and SV movements, tracked with total internal reflectance fluorescence microscopy. In contrast, coexpression of (Deltaexon3)hGH with GH-eGFP abolished the vesicular targeting of GH-eGFP, which instead accumulated in static aggregates. Transgenic mice expressing (Deltaexon3)hGH in somatotrophs showed an IGHD-II phenotype with mild to severe pituitary hypoplasia and dwarfism, evident at weaning in the most severely affected lines. Hypothalamic GHRH expression was up-regulated and somatostatin expression reduced in (Deltaexon3)hGH transgenic mice, consistent with their profound GHD. Few SVs were detectable in the residual pituitary somatotrophs in (Deltaexon3)hGH transgenic mice, and these cells showed grossly abnormal morphology. A low copy number transgenic line showed a mild effect relatively specific for GH, whereas two severely affected lines with higher transgene copy numbers showed early onset, widespread pituitary damage, macrophage invasion, and multiple hormone deficiencies. These new in vitro and in vivo models shed new light on the cellular mechanisms involved in IGHDII, as well as its phenotypic consequences in vivo.